2022
DOI: 10.21203/rs.3.rs-1586672/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variability studies on Fusarium sp. complex causing Pigeonpea wilt in India

Abstract: A total of 50 Fusarium isolates were collected from major pigeonpea growing states of India and studied for cultural and morphological characters. Among 50 isolates, a total of 30 isolates were selected based on their cultural and morphological characters and studied for pathogenic variability on eight pigeonpea (ICP8858, ICP 8859, ICP 8862, BDN-2, ICP 9174 ICP 8863, ICP 2376 and BAHAR) differential genotypes. Among eight genotypes, the four genotypes namely ICP8858, ICP 8859, ICP 8862, BDN-2 reacted different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Interestingly, recent reports indicate the occurrence of Perosomus Elumbis cases in local does in India Reddy et al (2017). documented cases of fetal monsters (Perosomus Elumbis), whileRavi et al (2011) reported Perosomus Elumbis cases with hydrocephalus in does in 2011.…”
mentioning
confidence: 99%
“…Interestingly, recent reports indicate the occurrence of Perosomus Elumbis cases in local does in India Reddy et al (2017). documented cases of fetal monsters (Perosomus Elumbis), whileRavi et al (2011) reported Perosomus Elumbis cases with hydrocephalus in does in 2011.…”
mentioning
confidence: 99%